Conductive paste and conductive film

By using tannin acid or its derivatives in the conductive paste, combined with copper powder and thermosetting resin, the problem of oxidation of copper paste under high humidity is solved, and the maintenance of conductivity over a long period of time is achieved and the humidity resistance is improved.

CN116323749BActive Publication Date: 2025-03-14GOO CHEM IND
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180062197.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-10
Filing Date
2021-09-07
Publication Date
2025-03-14
Estimated Expiration
2041-09-07

AI Technical Summary

Technical Problem

The existing copper paste is prone to oxidation under high humidity, resulting in a decrease in conductivity and it is difficult to maintain excellent conductivity for a long time.

Method used

Using a conductive paste containing tannin acid or its derivatives, combined with copper powder, thermosetting resin and solvent, the conductivity of the copper powder is enhanced and oxidation is inhibited by reducing and dispersibility of tannin acid.

Benefits of technology

It has excellent conductivity in the initial stage and can maintain excellent conductivity for a long period of time, reduce the increase in the specific resistance value, and improve moisture and heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004118698350000101
    Figure BDA0004118698350000101
  • Figure BDA0004118698350000131
    Figure BDA0004118698350000131
  • Figure BDA0004118698350000151
    Figure BDA0004118698350000151
Patent Text Reader

Abstract

Provided is a conductive paste having excellent initial conductivity and capable of maintaining excellent conductivity for a long time. The conductive paste comprises at least one of tannic acid and a tannic acid derivative (A), copper powder (B), a thermosetting resin (C), and a solvent (D).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a conductive paste and a conductive film, and in particular, to a conductive paste and a conductive film comprising a cured product of the conductive paste, the conductive paste comprising: a component (A) comprising at least one of tannic acid or a tannic acid derivative; a copper powder (B); a thermosetting resin (C); and a solvent (D). Background Art

[0002] A technique of printing a conductive paste on various types of base materials to form wiring is used. Conventionally known conductive pastes are mainly silver paste and copper paste. Silver paste has satisfactory conductivity but is expensive and tends to migrate therein under high humidity, thus causing a short circuit due to the migration problem. Therefore, it is considered to use copper paste instead of silver paste, but copper paste is more easily oxidized than silver paste, which therefore leads to a problem that the specific resistance value increases over time and the conductivity tends to decrease accordingly.

[0003] Suggested methods for suppressing oxidation of such a copper paste are, for example, a method of treating the surface of a copper powder with an organic substance in advance and a method of mixing an additive for suppressing copper oxidation into a composition containing a copper powder.

[0004] Patent document 1 discloses a method including: treating oxidizable metal fine particles with an aqueous surface treatment agent containing an organic acid in advance to effectively remove an oxide film formed on the surface of the metal fine particles; and further adding an organic carboxylic acid as an additive for inhibiting copper oxidation to a composition containing the treated copper powder. Patent document 2 discloses a method for inhibiting oxidation of copper powder by adding an organic carboxylic acid compound to a conductive copper paste containing copper powder so that protons are donated to the oxide film on the surface of the copper powder to elute the oxide film.

[0005] The method of treating copper powder with an organic acid is effective in removing the copper oxide coating already present on the copper powder to be used as a raw material, and thus is effective in showing conductivity in the initial stage, but this method is not sufficient to suppress oxidation over time. In addition, the method of adding an organic carboxylic acid compound is not sufficient to suppress the oxidation of the copper powder. Therefore, it is necessary to have a material that exhibits a further effective reducing ability for the copper powder, and that can exhibit the inherent conductivity of copper in the initial stage and can maintain the conductivity for a long time to ensure the reliability of the product.

[0006] Prior Art Literature

[0007] Patent Literature

[0008] Patent Document 1: JP 2014-011006 A

[0009] Patent Document 2: JP 2008-130301 A Summary of the invention

[0010] An object of the present disclosure is to provide a conductive paste and a conductive film having excellent conductivity in an initial stage and capable of maintaining excellent conductivity over a long period of time.

[0011] A conductive paste according to one aspect of the present disclosure includes a component (A) including at least one of tannic acid or a tannic acid derivative, a copper powder (B), a thermosetting resin (C), and a solvent (D).

[0012] A conductive film according to one aspect of the present disclosure includes a cured product of a conductive paste. DETAILED DESCRIPTION

[0013] <Conductive paste>

[0014] The conductive paste of the present embodiment (hereinafter also referred to as conductive paste (X)) comprises a component (A) (hereinafter also referred to as component (A)) comprising at least one of tannic acid or a tannic acid derivative, a copper powder (B), a thermosetting resin (C) and a solvent (D). The conductive paste (X) is heat curable and is therefore suitably applicable to forming a conductive film.

[0015] The present inventors have found that when the conductive paste containing copper powder as the metal powder contains tannic acid or its derivatives, the conductive paste has excellent conductivity in the initial stage and can maintain excellent conductivity for a long period of time. That is, the conductive paste (X) can have a reduced specific resistance value in the initial stage and can suppress oxidation over time (as evaluated by wet heat test, etc.), so that the conductive paste (X) can maintain conductivity for a long period of time. The reason is not necessarily clear, but it can be inferred that, for example, tannic acid and tannic acid derivatives make it possible to enhance the dispersibility of the copper powder (B) in the conductive paste (X) and the reducibility of tannic acid and tannic acid derivatives also make it possible to suppress the oxidation of the copper powder (B), and make it possible to reduce the copper oxide produced by the oxidation of copper to the initial copper, thereby restoring conductivity. In particular, when the thermosetting resin (C) is thermally cured, component (A) may show high reducing power, and the conductive paste (X) can show high conductivity in the initial stage, and in addition, the reducing power of component (A) makes it possible to maintain the high conductivity for a long period of time. Therefore, the conductive paste (X) has excellent conductivity in the initial stage and can maintain excellent conductivity for a long time.

[0016] [Component (A)]

[0017] Component (A) is at least one of tannic acid or tannic acid derivatives. "Tanninic acid" includes both tannic acid in a broad sense and m-galloylgallic acid (m-galloylgallic acid) which is tannic acid in a narrow sense. Tannic acid in a broad sense is a general term for aromatic compounds having a large number of phenolic hydroxyl groups, and examples thereof include condensed tannins that are derivatives of flavanols and hydrolyzable tannins having one or more gallic acids and sugars (usually glucose) bonded to each other by ester bonding. The number of phenolic hydroxyl groups per tannic acid molecule is generally greater than or equal to 3 and less than or equal to 100, preferably greater than or equal to 10 and less than or equal to 50, and more preferably greater than or equal to 20 and less than or equal to 30. The molecular weight of tannic acid is generally greater than or equal to 300 and less than or equal to 15,000, preferably greater than or equal to 500 and less than or equal to 5,000, and more preferably greater than or equal to 1,000 and less than or equal to 2,500.

[0018] The "tannic acid derivative" refers to, for example, a derivative obtained by replacing some or all of the hydrogen atoms in the phenolic hydroxyl group of tannic acid with a substituent (hereinafter also referred to as a substituent (S)). The tannic acid derivative is a derivative obtained by hydrophobizing tannic acid.

[0019] Component (A) preferably contains a tannic acid derivative. Using a tannic acid derivative obtained by hydrophobizing tannic acid as component (A) further enhances the effect of suppressing oxidation of the conductive paste (X) over time, and in particular, in a moisture and heat resistance test (e.g., 85°C, 85% RH, 100 hours), the increase in the specific resistance value can be further suppressed.

[0020] The tannic acid derivative preferably includes a derivative obtained by reacting some or all of the phenolic hydroxyl groups of tannic acid with a compound having an isocyanate group so as to form a carbamate bond. The introduction of a carbamate bond into the tannic acid derivative further improves the flexibility of the conductive film formed by the conductive paste (X), and therefore, it is expected that the conductive film will be applied to a flexible base material such as a film base material.

[0021] Alternatively, the tannic acid derivative is preferably a derivative obtained by reacting some or all of the phenolic hydroxyl groups of tannic acid with a silane coupling agent so as to form a -Si-O- bond. It is expected that the introduction of the -Si-O- bond into the tannic acid derivative further improves the dispersibility of the copper powder (B) and improves the adhesion between the conductive film formed by the conductive paste (X) and the base material.

[0022] Examples of the substituent (S) include: a hydrocarbon group, for example, an alkyl group such as a methyl group, a cycloalkyl group such as a cyclohexyl group, an aryl group such as a phenyl group, and an aralkyl group such as a benzyl group; a group obtained by replacing some or all of the hydrogen atoms of a hydrocarbon group with other substituents; -CONHR (R is a monovalent organic group having 1 to 20 carbon atoms); and -Si(OR')2R" (R' is a monovalent hydrocarbon group having 1 to 10 carbon atoms, and R" is a monovalent organic group having 1 to 20 carbon atoms). "Organic group" refers to a group containing at least one carbon atom.

[0023] The substituent (S) preferably includes a group having a polymerizable group. In this case, the curing shrinkage when the conductive paste (X) is thermally cured can be further improved, and therefore, the conductivity of the conductive film made of the conductive paste (X) can be further improved. Examples of polymerizable groups include (meth)acryloyl, vinyl, epoxy, glycidyl, amino and mercapto.

[0024] -CONHR as the substituent (S) is formed by reacting tannic acid with a compound having an isocyanate group. Examples of the organic group represented by R include: a monovalent hydrocarbon group such as a substituted or unsubstituted butyl group; a group containing a polymerizable group such as a (meth)acryloyl group, a vinyl group, and a glycidyl group. When R is a group containing a polymerizable group, the curing shrinkage when the conductive paste (X) is thermally cured can be further increased, and therefore, the conductivity of the conductive film made of the conductive paste (X) can be further improved.

[0025] -Si(OR')2R" as the substituent (S) is formed by reacting tannic acid with a silane coupling agent. Examples of the hydrocarbon group represented by R' include alkyl groups such as methyl and ethyl groups. Examples of the organic group represented by R" include: a substituted or unsubstituted monovalent hydrocarbon group; and a group containing a polymerizable group such as a glycidyl group, an epoxy group, a (meth)acryloyl group, a vinyl group, an amino group and a mercapto group. When R" is a group containing a polymerizable group, the curing shrinkage when the conductive paste (X) is thermally cured can be further improved, and therefore, the conductivity of the conductive film made of the conductive paste (X) can be further improved.

[0026] The substitution rate of the tannic acid derivative (the ratio of the number of substituents (S) per tannic acid derivative molecule to the number of phenolic hydroxyl groups per tannic acid molecule before substitution) is preferably higher than or equal to 10%. In this case, the moisture and heat resistance of the conductive paste (X) can be further effectively improved. The substitution rate is more preferably higher than or equal to 15%, further more preferably higher than or equal to 20%, and particularly preferably higher than or equal to 30%. The substitution rate in the tannic acid derivative is preferably lower than or equal to 65%. In this case, the effect of suppressing oxidation of the conductive paste (X) can be further improved. The substitution rate is more preferably lower than or equal to 60%, further more preferably lower than or equal to 55%, and particularly preferably lower than or equal to 50%.

[0027] The ratio of component (A) to 100 parts by mass of copper powder (B) is preferably greater than or equal to 0.05 parts by mass and less than or equal to 5.0 parts by mass. In this case. The conductivity and continuity of the conductive paste (X) can be further improved. The ratio of component (A) to 100 parts by mass of copper powder (B) is more preferably greater than or equal to 0.1 parts by mass and less than or equal to 3.0 parts by mass, further more preferably greater than or equal to 0.4 parts by mass and less than or equal to 2.0 parts by mass, and particularly preferably greater than or equal to 0.5 parts by mass and less than or equal to 1.2 parts by mass.

[0028] The ratio of component (A) to the conductive paste (X) is preferably greater than or equal to 0.01% by mass and less than or equal to 10% by mass, more preferably greater than or equal to 0.05% by mass and less than or equal to 5% by mass, further more preferably greater than or equal to 0.1% by mass and less than or equal to 3% by mass, and particularly preferably greater than or equal to 0.4% by mass and less than or equal to 1.5% by mass.

[0029] [Copper powder (B)]

[0030] The copper powder (B) is metal particles containing copper as a main component, wherein copper is exposed on the particle surface.

[0031] Examples of the shape of the copper powder (B) include a spherical shape, a flat shape (scaly shape), a dendritic shape, and an amorphous shape. The copper powder (B) may be in a combination of two or more of these shapes. The excellent conductivity and oxidation resistance of the conductive paste (X) are attributed to the excellent reducing ability of component (A) to copper, and the shape and particle size of the copper powder (B) are not particularly limited.

[0032] From the viewpoint of printing suitability, the average particle size of the copper powder (B) is preferably greater than or equal to 0.1 μm and less than or equal to 30 μm, more preferably greater than or equal to 0.5 μm and less than or equal to 20 μm, and further more preferably greater than or equal to 1 μm and less than or equal to 10 μm. The average particle size is a median diameter, and the particle size distribution (volume basis) of the copper powder (B) is measured, and the particle size in the cumulative distribution of 50 volume % thereof is shown.

[0033] The ratio of the copper powder (B) to the conductive paste (X) is preferably greater than or equal to 50% by mass and less than or equal to 99% by mass, more preferably greater than or equal to 60% by mass and less than or equal to 98% by mass, further more preferably greater than or equal to 70% by mass and less than or equal to 95% by mass, and particularly preferably greater than or equal to 80% by mass and less than or equal to 90% by mass.

[0034] [Thermosetting resin (C)]

[0035] The conductive paste (X) contains a thermosetting resin (C). Therefore, heating enables the conductive paste (X) to be cured to form a conductive film.

[0036] Examples of the thermosetting resin (C) include amino resins, urethane resins, unsaturated polyester resins, epoxy resins, cyanate resins, acrylic resins, and phenolic resins such as novolac phenolic resins or resol phenolic resins. The thermosetting resin (C) does not contain tannic acid and tannic acid derivatives.

[0037] The thermosetting resin (C) preferably includes a resin having a phenolic hydroxyl group. In this case, the curing shrinkage caused by the heat curing of the thermosetting resin (C) can be further improved, and therefore, the conductivity of the conductive paste (X) can be further improved. Examples of the thermosetting resin (C) having a phenolic hydroxyl group include phenolic resins.

[0038] The ratio of the thermosetting resin (C) to the conductive paste (X) is preferably greater than or equal to 1% by mass and less than or equal to 30% by mass, more preferably greater than or equal to 3% by mass and less than or equal to 20% by mass, and further more preferably greater than or equal to 5% by mass and less than or equal to 15% by mass.

[0039] Furthermore, the conductive paste (X) may contain, for example, a curing agent and a curing accelerator to promote curing of the thermosetting resin (C).

[0040] As the curing agent, any curing agent can be used as long as it can cure the thermosetting resin (C), and examples of the curing agent include: novolac resin; curing agents based on latent amines such as dicyandiamide, imidazole, BF3-amine complex and guanidine derivatives; aromatic amines such as metaphenylenediamine, diaminodiphenylmethane and diaminodiphenylsulfone; curing agents containing nitrogen atoms such as cyclophosphazene oligomers; and curing agents based on acid anhydrides such as polyamide resins, maleic anhydride, phthalic anhydride, hexahydrophthalic anhydride and pyromellitic anhydride. The ratio of the curing agent to the thermosetting resin (C) is generally greater than or equal to 0.1% by mass and less than or equal to 10% by mass, and preferably greater than or equal to 0.5% by mass and less than or equal to 5% by mass.

[0041] Examples of curing accelerators include tertiary amines such as benzyldimethylamine; imidazoles; organic acid metal salts; Lewis acids; and amine complex salts. The ratio of the curing accelerator to the thermosetting resin (C) is usually greater than or equal to 0.01% by mass and less than or equal to 10% by mass, and preferably greater than or equal to 0.1% by mass and less than or equal to 5% by mass.

[0042] [Solvent (D)]

[0043] The conductive paste (X) contains the solvent (D). This enables the viscosity of the conductive paste (X) to be adjusted more appropriately, and thus the conductive paste (X) is suitably applicable to screen printing and the like.

[0044] Examples of the solvent (D) include: polyols such as diols (e.g., ethylene glycol, propylene glycol and dipropylene glycol) and triols (e.g., glycerol); sugar alcohols; lower alcohols such as ethanol, methanol, butanol, propanol and isopropanol; 1-methyl-1-methoxybutanol; cellosolves such as ethylene glycol monomethyl ether (methyl cellosolve), ethylene glycol monoethyl ether (ethyl cellosolve), ethylene glycol monoisopropyl ether (isopropyl cellosolve), ethylene glycol mono-n-butyl ether (n-butyl cellosolve) and ethylene glycol mono-tert-butyl ether (tert-butyl cellosolve); carbitols such as diethylene glycol monomethyl ether (methyl carbitol); diethylene glycol monoethyl ether (ethyl carbitol), diethylene glycol mono-n-propyl ether (n-propyl carbitol); diethylene glycol monoisopropyl ether (isopropyl carbitol), ethylene glycol Mono-n-butyl ether (n-butyl carbitol), diethylene glycol mono-tert-butyl ether (tert-butyl carbitol); triethylene glycol such as triethylene glycol monoethyl ether (ethyl triethylene glycol); propylene glycol monoethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-tert-butyl ether, propylene glycol mono-n-propyl ether and propylene glycol monoisopropyl ether; dipropylene glycol monoethers such as dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol mono-n-propyl ether and dipropylene glycol monoisopropyl ether; glycol ethers such as tripropylene glycol monoether (e.g., tripropylene glycol monomethyl ether); glycol ether carboxylates such as cellosolve carboxylates (e.g., ethylene glycol monomethyl ether acetate); and alkanolamines such as ethanolamine, diethanolamine and triethanolamine.

[0045] The solvent (D) preferably includes a solvent having an alcoholic hydroxyl group. In this case, the solvent (D) can satisfactorily dissolve the component (A), which makes it possible to further improve the oxidation inhibition effect provided by the component (A). In addition, since the solvent (D) having an alcoholic hydroxyl group exhibits reducing properties when thermally cured, the solvent (D) can further improve the oxidation inhibition effect provided by the component (A).

[0046] From the viewpoint of solubility of tannic acid, printability and the like, the solvent (D) preferably includes at least one selected from lower alcohols and glycol ethers, and more preferably includes at least one selected from methanol, ethanol and ethyl carbitol.

[0047] From the viewpoint of further appropriately adjusting the viscosity of the conductive paste (X), the ratio of the solvent (D) to the conductive paste (X) is preferably greater than or equal to 0.1% by mass and less than or equal to 10% by mass, more preferably greater than or equal to 1% by mass and less than or equal to 8% by mass, and further more preferably greater than or equal to 3% by mass and less than or equal to 7% by mass.

[0048] [Boric acid]

[0049] In addition to orthoboric acid (H3BO3), examples of boric acid also include metaboric acid and tetraboric acid, which are condensates of orthoboric acid (H3BO3). The conductive paste (X) preferably comprises boric acid. This makes it possible to further reduce the specific resistance value of the conductive paste (X). In addition, when the thermosetting resin (C) has a hydroxyl group, the hydrogen bond formed between the hydroxyl group and the boric acid makes it possible to further reduce the specific resistance value. In addition, since boric acid also forms a hydrogen bond with the phenolic hydroxyl group of component (A), a network of thermosetting resin (C)-boric acid-tannic acid is formed, which makes it possible to further improve conductivity.

[0050] The ratio of boric acid to the sum of component (A) thermosetting resin (C) (including curing agent and curing accelerator) is preferably 1.0 mass % or more and 40 mass % or less, more preferably 2 mass % or more and 20 mass % or less.

[0051] The ratio of boric acid to the conductive paste (X) is preferably greater than or equal to 0.1% by mass and less than or equal to 4% by mass, more preferably greater than or equal to 0.2% by mass and less than or equal to 2% by mass.

[0052] [Other components]

[0053] The conductive paste (X) may contain, for example, a rust preventive, an antioxidant, an adhesion imparting agent, a dispersant, a chelating agent, a leveling agent, a thixo adjusting agent, and a defoaming agent as other components. The ratio of other components to the conductive paste (X) is, for example, less than or equal to 2 mass %.

[0054] (Viscosity)

[0055] The viscosity of the conductive paste (X) at 25°C is preferably greater than or equal to 5.0Pa·s and less than or equal to 200Pa·s. In this case, the conductive paste (X) is easily printed, does not impair the processability of screen printing, and is easy to form wiring in a satisfactory pattern. The thixotropic ratio (Ti value) of the conductive paste (X) is preferably greater than or equal to 1.0 and less than or equal to 3.0. In this case, the conductive paste (X) does not impair the processability of screen printing, and is easy to form wiring in a satisfactory pattern. The thixotropic ratio is expressed as the ratio of the viscosity at 25°C and 0.5rpm to the viscosity at 25°C and 5rpm (thixotropic ratio = (viscosity at 25°C, 0.5rpm) / (viscosity at 25°C, 5rpm)).

[0056] <Conductive film>

[0057] The conductive film of the present embodiment comprises a cured product of the conductive paste (X). Since the conductive film of the present embodiment is formed of the conductive paste (X), the conductive film has excellent conductivity in the initial stage and can maintain excellent conductivity for a long period of time. In addition, when the conductive paste (X) comprises boric acid and a tannic acid derivative having a carbamate bond, the conductive film is also excellent in folding resistance.

[0058] The conductive film of the present embodiment is formed by applying a conductive paste (X) to a base material such as a glass plate or a PET film via, for example, screen printing, and then curing the conductive paste (X) by heating. The heating temperature and the heating time period are appropriately selected according to the type of thermosetting resin (C), wherein the heating temperature is generally higher than or equal to 100°C and lower than or equal to 250°C, and preferably higher than or equal to 130°C and lower than or equal to 200°C. The heating time period is generally longer than or equal to 1 minute and shorter than or equal to 5 hours, and preferably longer than or equal to 10 minutes and shorter than or equal to 1 hour. The shape of the conductive film is not particularly limited, and in addition to being a line shape or a strip shape such as a circuit pattern in a plan view, examples of the shape also include a circular shape and a quadrilateral shape in a plan view. The thickness of the conductive film is, for example, greater than or equal to 1 μm and less than or equal to 1 mm, preferably greater than or equal to 5 μm and less than or equal to 100 μm, and more preferably greater than or equal to 10 μm and less than or equal to 50 μm.

[0059] Example

[0060] The present disclosure will be specifically described with reference to the following examples.

[0061] <Synthesis of Tannic Acid Derivatives>

[0062] In a four-necked flask equipped with a reflux condenser, a thermometer, a nitrogen introduction tube and a stirrer, 100 g of tannic acid (manufactured by Fuji Chemical Industries Co., Ltd., trade name: "tannic acid", the total number of hydroxyl groups per tannic acid molecule is 25) and 100 g of methyl ethyl ketone were placed and dissolved by mixing to obtain a solution. 82 g of ethyl acrylate isocyanate (manufactured by Showa Denko KK, trade name: "Karenz AOI") as an isocyanate compound was mixed with the solution and reacted at 60° C. for 5 hours. Methyl ethyl ketone was evaporated from the solution and dried to obtain a tannic acid derivative (1).

[0063] In the same manner, 141 g of an isocyanate compound was reacted with the solution to obtain a tannic acid derivative (2), 24 g of an isocyanate compound was reacted with the solution to obtain a tannic acid derivative (3), 160 g of an isocyanate compound was reacted with the solution to obtain a tannic acid derivative (4), and 65 g of butyl isocyanate was reacted with the solution as an isocyanate compound to obtain a tannic acid derivative (5), and 36 g of a silane coupling agent (manufactured by Dow Toray Co., Ltd., trade name: "Xiameter OFS-6040 Silane", glycidyloxypropyltrimethoxysilane) was reacted with the solution to obtain a tannic acid derivative (6). The weight average molecular weight of the tannic acid derivative thus obtained was measured by the GPC measurement method shown below.

[0064] (Measurement of weight average molecular weight)

[0065] The weight average molecular weight was determined by the GPC method based on standard polystyrene. The measurement conditions are shown below.

[0066] · Device: "Prominence LC-20AD" manufactured by SHIMADZU CORPORATION

[0067] · Column: A total of three columns "GPC KF-801, GPC KF-803, GPC KF-805" manufactured by Showa Denko KK

[0068] Guard column: "GPC-KF-G 4A" manufactured by Showa Denko KK

[0069] Sample concentration: The sample was diluted with tetrahydrofuran so that the concentration of tannic acid or a tannic acid derivative became 0.5% by mass.

[0070] Mobile phase solvent: tetrahydrofuran

[0071] Flow rate: 1.0mL / min

[0072] Column temperature: 40℃

[0073] Table 1 below collectively shows the weight average molecular weight of each of the tannic acid derivatives and tannic acid thus synthesized and the substitution ratio of hydrogen atoms of the phenolic hydroxyl group of each tannic acid derivative.

[0074] [Table 1]

[0075]

[0076] <Preparation of Conductive Paste>

[0077] (Example 1)

[0078] 0.40 g of tannic acid derivative (1), 4.6 g of epoxy resin (manufactured by DIC Corporation, EPICLONEXA4816), 0.02 g of curing accelerator (manufactured by SHIKOKU CHEMICALS CORPORATION, CUREZOL 2PHZ-PW) and 0.5 g of boric acid were blended and dissolved in 3.0 g of ethyl carbitol as a solvent to obtain a resin solution. 48.0 g of copper particles (manufactured by FUKUDA METAL FOIL & POWDER CO., LTD., trade name: "Cu-HWF-4") were blended in the resin solution, mixed by using a mixing stirrer, and then kneaded by using a roll mill to obtain a conductive paste 1 (DP-1).

[0079] (Example 2)

[0080] Conductive paste 2 (DP-2) was obtained in the same manner as in Example 1, except that boric acid was not blended.

[0081] (Example 3)

[0082] Conductive paste 3 (DP-3) was obtained in the same manner as in Example 1, except that tannic acid was used instead of the tannic acid derivative (1).

[0083] (Example 4)

[0084] Conductive paste 4 (DP-4) was obtained in the same manner as in Example 1, except that the tannic acid derivative (6) was used.

[0085] (Example 5)

[0086] Conductive paste 5 (DP-5) was obtained in the same manner as in Example 2, except that a resol resin (manufactured by MEIWA PLASTIC INDUSTRIES, LTD., trade name: "MWF-2620", solid content: 70 mass %) was used as a thermosetting resin instead of the epoxy resin and the curing accelerator.

[0087] (Example 6)

[0088] Conductive paste 6 (DP-6) was obtained in the same manner as in Example 1, except that the tannic acid derivative (2) was used.

[0089] (Example 7)

[0090] Conductive paste 7 (DP-7) was obtained in the same manner as in Example 1, except that ethyl carbitol acetate was used instead of the solvent.

[0091] (Example 8)

[0092] Conductive paste 8 (DP-8) was obtained in the same manner as in Example 1, except that the tannic acid derivative (3) was used.

[0093] (Example 9)

[0094] Conductive paste 9 (DP-9) was obtained in the same manner as in Example 1, except that the tannic acid derivative (4) was used.

[0095] (Example 10)

[0096] Conductive paste 10 (DP-10) was obtained in the same manner as in Example 1, except that the tannic acid derivative (5) was used.

[0097] (Comparative Example 1)

[0098] Conductive paste 11 (DP-11) was obtained in the same manner as in Example 1, except that tannic acid and tannic acid derivatives were not added.

[0099] [Evaluation of conductive paste]

[0100] (Viscosity measurement and Ti value)

[0101] The viscosity of the conductive paste obtained in each of Examples 1 to 9 and Comparative Example 1 at 25° C. was measured by a cone-plate viscometer (manufactured by Toki Sangyo Co., Ltd) (at 5 rpm and 0.5 rpm). Furthermore, from these measured values, the Ti value (=viscosity at 0.5 rpm / viscosity at 5 rpm) was determined.

[0102] (Evaluation of dispersibility of copper powder)

[0103] In order to evaluate the dispersibility of the copper powder in each of the thus obtained conductive pastes, the coarse particles were examined by using a grind gauge (manufactured by Taiyu Kizai Co. Ltd., "GM-7470", 0 μm to 25 μm) and referring to JIS K5600-2-5 (fineness of grinding).

[0104] From the examination results of the coarse granules, the dispersibility of the copper powder was evaluated based on the following criteria.

[0105] A: The result determined by the fineness meter is less than or equal to 7.5μm.

[0106] B: The result determined by a fineness meter is 10.0 μm.

[0107] C: The result determined by the fineness meter is greater than or equal to 12.5 μm.

[0108] Table 2 below collectively shows the measured values ​​(Pa·s) of the paste viscosity (at 5 rpm and 0.5 rpm) and the Ti value, and the evaluation results of the dispersibility of the copper powder.

[0109] [Table 2]

[0110]

[0111] <Formation of Conductive Film>

[0112] The conductive pastes 1 to 11 (DP-1 to DP-11) thus obtained were applied to a PET film by screen printing in a strip wiring shape having a width of 1 mm, a length of 50 mm and a thickness of 20 μm, and then cured by heating it at 150° C. for 30 minutes, thereby obtaining base materials 1 to 11 respectively provided with conductive films 1 to 11 (DM-1 to DM-11).

[0113] [Evaluation of conductive film]

[0114] (Measurement of the resistance value of the conductive film)

[0115] The resistance values ​​(Ω) of the conductive films 1 to 11 (DM-1 to DM-11) thus obtained were measured by using a four-point resistance meter (manufactured by HIOKI EE CORPORATION, resistance meter RM3544-01).

[0116] (Durability test)

[0117] The base materials 1 to 11 provided with the conductive films were subjected to a durability test in a high temperature and high humidity environment. In other words, the base materials provided with the conductive films 1 to 11 (DM-1 to DM-11) were stored in a tank at a high temperature of 85°C and a high humidity of 85%RH for 100 hours, and then the resistance values ​​of the conductive films 1 to 11 (DM-1 to DM-11) were measured to calculate the specific resistance value after the durability test.

[0118] (Evaluation of folding resistance)

[0119] The thus obtained conductive films 1 to 11 (DM-1 to DM-11) were folded by winding around an iron core of 2 mmΦ and then unfolded by using a folding tester, after which specific resistance values ​​of the conductive films were measured. The folding resistance was evaluated based on the following criteria.

[0120] S: The increase rate of the specific resistance value before and after folding is less than or equal to 20%.

[0121] A: The increase rate of the specific resistance value before and after folding is more than 20% and less than or equal to 40%.

[0122] B: The increase rate of the specific resistance value before and after folding is more than 40% and less than or equal to 100%.

[0123] C: The increase rate of the specific resistance value before and after folding is greater than 100%.

[0124] The following Table 3 collectively shows the resistance value (Ω) of the conductive film, the film thickness (μm) of the conductive film, the specific resistance value (volume resistivity) (μΩ·cm) calculated from the resistance value and the film thickness, the specific resistance value after the durability test (μΩ·cm), the durability test change rate (= (specific resistance value after the durability test / specific resistance value before the durability test-1)×100(%)) and the evaluation results of folding resistance.

[0125] [Table 3]

[0126]

[0127] As can be seen from the results shown in Tables 2 and 3, the conductive film formed by the conductive paste of the embodiment has excellent conductivity in the initial stage and can maintain excellent conductivity for a long period of time. In particular, the conductive pastes of Examples 1 to 5 are excellent in dispersibility of copper powder, and in particular, the conductive pastes of Examples 1, 3, 4 and 5 have a low resistivity of about 100 μΩ·cm and can provide an excellent conductive film. In addition, Examples 1, 2, 4, 5, 6, 7, 8 and 10 using tannic acid derivatives with a substitution rate of 10% to 65% can provide a conductive film with excellent durability. The conductive paste of Comparative Example 1 has poor dispersibility of copper powder and has a high specific resistance value of the conductive film in the initial stage, and therefore, it seems to have been oxidized in the step of preparing the conductive paste. In addition, in the moisture resistance test, the specific resistance value also increases.

[0128] Furthermore, as can be seen from the results shown in Table 3, the conductive films formed of the conductive pastes obtained by combining the tannic acid derivative having a urethane bond and boric acid in Examples 1, 6, 7, 9, and 10 had satisfactory folding resistance.

[0129] The conductive paste of Example 9 using the tannic acid derivative in which the substitution rate of hydrogen atoms of the phenolic hydroxyl group exceeds a certain value has an increased specific resistance value at the initial stage, reduced dispersibility of copper powder, and a specific resistance value with a high rising rate after the durability test, and thus, the effect of the tannic acid derivative may be reduced. The conductive paste of Example 7 does not use a solvent having a hydroxyl group, and thus, the rust-proof effect of the tannic acid derivative when preparing the paste may be reduced.

[0130] (Summarize)

[0131] As can be seen from the foregoing, the conductive paste according to the first aspect of the present disclosure includes a component (A) including at least one of tannic acid or a tannic acid derivative, a copper powder (B), a thermosetting resin (C), and a solvent (D).

[0132] According to the first aspect, the conductive paste has excellent conductivity in the initial stage and can maintain the excellent conductivity for a long time.

[0133] In the conductive paste of the second aspect related to the first aspect, component (A) contains a tannic acid derivative, and the tannic acid derivative is a derivative obtained by substituting hydrogen atoms in some phenolic hydroxyl groups of tannic acid with a substituent at a substitution rate of 10% or more and 65% or less.

[0134] The second aspect enables further enhancement of the effect of suppressing oxidation of the conductive paste over time, in particular, enables further suppression of an increase in specific resistance in a moisture and heat resistance test, and enables more effective improvement of moisture and heat resistance.

[0135] In the conductive paste of the third aspect related to the first aspect, component (A) contains a tannic acid derivative, and the tannic acid derivative is a derivative obtained by reacting some or all of phenolic hydroxyl groups of tannic acid with a compound having an isocyanate group so that a urethane bond is formed.

[0136] According to the third aspect, the effect of suppressing oxidation over time is further enhanced, and in particular, the increase in resistivity is further suppressed in a moisture and heat resistance test. Furthermore, the introduction of carbamate bonds into the tannic acid derivative improves the flexibility of the conductive film formed by the conductive paste, making it expected that the conductive film will be applied to flexible base materials such as film base materials.

[0137] The conductive paste of the fourth aspect relating to any one of the first to third aspects further contains boric acid.

[0138] The fourth aspect enables the specific resistance value of the conductive paste to be further reduced. In addition, when the thermosetting resin (C) has a hydroxyl group, the hydrogen bond formed between the hydroxyl group and the boric acid enables the specific resistance value to be further reduced. In addition, since the boric acid also forms a hydrogen bond with the phenolic hydroxyl group of the component (A), a network of thermosetting resin (C)-boric acid-tannic acid is formed, which enables the conductivity to be further improved.

[0139] The conductive paste of the fifth aspect related to any one of the first to fourth aspects further contains a solvent (D) having an alcoholic hydroxyl group.

[0140] According to the fifth aspect, the solvent (D) can satisfactorily dissolve the component (A), which makes it possible to further improve the oxidation inhibition effect provided by the component (A). In addition, since the solvent (D) having an alcoholic hydroxyl group exhibits reducing properties during thermal curing, the solvent (D) can further improve the oxidation inhibition effect provided by the component (A).

[0141] In the conductive paste of a sixth aspect related to any one of the first to fifth aspects, the thermosetting resin (C) has a phenolic hydroxyl group.

[0142] According to the sixth aspect, the curing shrinkage due to the thermal curing of the thermosetting resin (C) is further increased, and thus, the conductivity of the conductive paste (X) is further improved.

[0143] The conductive film of the seventh aspect comprises a cured product of the conductive paste of any one of the first to sixth aspects.

[0144] According to the seventh aspect, the conductive film has excellent conductivity in the initial stage and can maintain the excellent conductivity for a long time.

[0145] Industrial Applicability

[0146] According to the conductive paste of the present disclosure, thermal curing enables formation of a conductive film having excellent conductivity in the initial stage, having excellent moisture resistance, and being able to maintain excellent conductivity for a long time without using special equipment requiring an inert gas or the like.

Claims

1. A conductive paste comprising: Tannic acid derivatives (A); Copper powder (B); Thermosetting resin (C); and Solvent (D), The tannic acid derivative (A) is a derivative obtained by replacing hydrogen atoms in some of the phenolic hydroxyl groups of tannic acid with a substituent at a substitution rate of 10% or more and 65% or less.

2. A conductive paste comprising: Tannic acid derivatives (A); Copper powder (B); Thermosetting resin (C); and Solvent (D), The tannic acid derivative (A) is a derivative obtained by reacting some or all of the phenolic hydroxyl groups of tannic acid with a compound having an isocyanate group so that a urethane bond is formed. The conductive paste according to claim 1 or 2, further comprising boric acid.

4. The conductive paste according to claim 1 or 2, wherein The solvent (D) has an alcoholic hydroxyl group.

5. The conductive paste according to claim 3, wherein The solvent (D) has an alcoholic hydroxyl group.

6. The conductive paste according to claim 1 or 2, wherein The thermosetting resin (C) has a phenolic hydroxyl group.

7. The conductive paste according to claim 3, wherein The thermosetting resin (C) has a phenolic hydroxyl group. 8 . A conductive film comprising a cured product of the conductive paste according to claim 1 .

Citation Information

Patent Citations

  • Conductive copper paste

    JP2008130301A

  • Conductive inks and manufacturing method thereof

    CN101010388A

  • Electronic paste for mobile phone touch screen and preparation method thereof

    CN104123974A

  • Conductive paste composition

    JP1991007780A

  • Manufacture of electronic part and conductive paste used therefor

    JP1998074661A